2003
DOI: 10.1167/iovs.02-1228
|View full text |Cite
|
Sign up to set email alerts
|

Scleral Plug of Biodegradable Polymers Containing Tacrolimus (FK506) for Experimental Uveitis

Abstract: Intravitreal sustained-release of FK506 from a biodegradable polymeric scleral plug was highly effective in suppressing the inflammation of experimental uveitis in a rabbit model for at least 6 weeks. This device may be useful in the management of patients with severe chronic uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 12 publications
1
37
0
5
Order By: Relevance
“…25,26 Souza et al 25 reported an intravitreal tacrolimus-loaded poly(d,l-lactide-coglycolide) (PLGA) implant provided prolonged release of drug up to 6 weeks, and there was no evidence of toxic effects of implants. Sakurai et al 26 also reported a scleral PLGA plug containing tacrolimus was effective in suppressing the inflammation of experimental uveitis in a rabbit model for at least 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Souza et al 25 reported an intravitreal tacrolimus-loaded poly(d,l-lactide-coglycolide) (PLGA) implant provided prolonged release of drug up to 6 weeks, and there was no evidence of toxic effects of implants. Sakurai et al 26 also reported a scleral PLGA plug containing tacrolimus was effective in suppressing the inflammation of experimental uveitis in a rabbit model for at least 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Souza et al 25 reported an intravitreal tacrolimus-loaded poly(d,l-lactide-coglycolide) (PLGA) implant provided prolonged release of drug up to 6 weeks, and there was no evidence of toxic effects of implants. Sakurai et al 26 also reported a scleral PLGA plug containing tacrolimus was effective in suppressing the inflammation of experimental uveitis in a rabbit model for at least 6 weeks. 26 Compared to those designs, the subconjunctival microfilm reported in the present study is more ideal for conjunctival diseases like allergic conjunctivitis, and this is the first described tacrolimus drug delivery system inserted subconjunctivally to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…26 There are also reports of trans-scleral delivery of betamethasone from implant devices, 15 sodium fl uorescein, 27 and ganciclovir. 28 One of the proposed barriers to trans-scleral delivery is represented by the choroidal blood fl ow clearance mechanism. Perhaps, the ovalbumin protein is large enough to breach this clearance mechanism and escapes rapid removal by the choroidal blood.…”
Section: Discussionmentioning
confidence: 99%
“…A biocompatibilidade e a biodegradação in vivo de implantes intravítreos preparados com diferentes ésteres de ácido hialurônico foi avaliada em olhos de coelhos (Avitabile et al, 2001 A segurança e a eficácia de um sistema biodegradável composto de PLGA e contendo 0,5 mg de ciclosporina (CsA) foram avaliadas após sua implantação na câmara anterior de olhos de coelhos (Theng et al, 2003 A eficácia de um implante polimérico biodegradável contendo tacrolimus foi avaliada em um modelo animal de uveíte experimental (Sakurai et al, 2003 A uveíte recorrente equina (URE), também conhecida como cegueira da lua, iridociclite e oftalmia periódica é a causa mais comum de cegueira em BIONDI, F. et al Implantes poliméricos intraoculares de fármacos na medicina veterinária, revisão de literatura e relato de um caso. PUBVET, Londrina, V. 6, N. 23, Ed.…”
Section: Desenvolvimentounclassified
“…210, Art. 1399, 2012 em severos efeitos adversos (Fialho e Cunha Júnior, 2007 Devido a todas as dificuldades encontradas, algumas pesquisas têm sido realizadas no sentido de desenvolver sistemas de administração intraoculares que permitam liberar concentrações terapêuticas dos fármacos por um período prolongado e adequado (Rubsamen et al, 1994;Hashizoe et al, 1994;Chang e Wong, 1999;Gilger et al, 2000;Avitabile et al, 2001;Okabe et al, 2003;Sakurai et al, 2003;Saliba et al, 2008;Choonara et al, 2011;Haghjou et al, 2011). Tais sistemas podem proporcionar inúmeras vantagens, como aumentar a biodisponibilidade do fármaco, no sentido de obter uma liberação constante e prolongada; aumentar as concentrações locais, sem a ocorrência de efeitos adversos sistêmicos; atingir mais especificamente um tipo de tecido ou célula; reduzir a freqüência de injeções intraoculares.…”
Section: Introductionunclassified